2015
DOI: 10.1155/2015/312530
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of theIn VivoandIn VitroEffects of Fructose on Respiratory Chain Complexes in Tissues of Young Rats

Abstract: Hereditary fructose intolerance (HFI) is an autosomal-recessive disorder characterized by fructose and fructose-1-phosphate accumulation in tissues and biological fluids of patients. This disease results from a deficiency of aldolase B, which metabolizes fructose in the liver, kidney, and small intestine. We here investigated the effect of acute fructose administration on the activities of mitochondrial respiratory chain complexes, succinate dehydrogenase (SDH), and malate dehydrogenase (MDH) in cerebral corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Similar to our previous findings from males, the current results suggest that consumption of SSBs also has a negative impact on hair health in women, and demonstrate that intaking more than 7 times or 1000 mL per week significantly increased the risk of hair loss. This relationship could be explained by the high blood sugar levels, caused by excessive consumption of SSBs, which may trigger a lack of energy in the outer root sheath keratinocytes of women, considered a possible cause of excessive hair shedding [9][10][11]26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our previous findings from males, the current results suggest that consumption of SSBs also has a negative impact on hair health in women, and demonstrate that intaking more than 7 times or 1000 mL per week significantly increased the risk of hair loss. This relationship could be explained by the high blood sugar levels, caused by excessive consumption of SSBs, which may trigger a lack of energy in the outer root sheath keratinocytes of women, considered a possible cause of excessive hair shedding [9][10][11]26].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary habits are important influential factors in hair loss. Compelling evidence from laboratory and animal research suggested that excessive added sugar intake can provide a higher glucose concentration in serum, which triggers the polyol pathway by creating a high affinity for aldose reductase to cause a lack of energy in outer root sheath keratinocytes [9][10][11]. Our previous study found that excessive consumption of sugar-sweetened beverages (SSBs, a major dietary source of added sugars) is associated with a significant high risk of male pattern hair loss (MPHL) [12].…”
Section: Xj Shi Et Al / Food Science and Humanmentioning
confidence: 99%
“…With a continuous glucose supply, the polyol pathway is reinforced by a positive feedback loop [ 56 ]. In vitro and in vivo studies have shown that glucose utilization in the polyol pathway reduces the amount of glucose available to the outer root sheath keratinocytes of hair follicles, and gluconeogenesis is also antagonized by depletion of ATP and phosphate levels [ 19 , 57 ]. Lack of energy in outer root sheath keratinocytes is considered a possible cause of MPHL.…”
Section: Discussionmentioning
confidence: 99%